Waterproof oil-control powder with soft coke effect as well as preparation method and application of waterproof oil-control powder
By developing a waterproof and oil-controlling powder containing synthetic fluorogen mica and other ingredients, the shortcomings of existing makeup products in oil control, waterproof and natural makeup are solved, and the versatility of oil control, waterproof and soft focus is achieved, and the naturalness and durability of makeup are improved.
Patent Information
- Application Number
- CN202510086434.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing makeup products have shortcomings in oil control and waterproofing, and often appear thick and masked, which cannot meet the needs of modern consumers for light and natural makeup.
Develop a waterproof and oil-controlling powder with soft focus effect, and achieve the versatility of oil-control, waterproofing and soft focus by synthesizing a combination of fluorogold mica, vinyl polydimethylsiloxane/polymethylsiloxane silsesquioxane cross-linked polymer, silica, triethoxyoctylsilane, zinc oxide, trimethylsiloxy silicate and octanyl glycine.
This powder not only has good oil control and waterproofing effects, but also improves the skin texture through soft focus effect, making the makeup more natural and lasting, and meeting the needs of modern consumers for high-quality cosmetics.
Smart Images

Figure BDA0005250255390000061 
Figure BDA0005250255390000071 
Figure BDA0005250255390000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cosmetics, and in particular to a waterproof and oil-controlling powder with a soft-focus effect, and a preparation method and application thereof. Background Art
[0002] In daily life, human skin naturally secretes oil, especially on the forehead, nose, chin, etc. For people who wear makeup, excessive sebum secretion will cause the makeup to lose its luster, and even cause makeup to come off, smudge, and other undesirable phenomena. Therefore, an important function of makeup products is to control oil to keep the makeup durable and fresh.
[0003] In order to solve the above problems, traditional makeup products often achieve oil control by adding oil-absorbing powders, but these powders are usually not waterproof and easily lose their effectiveness when sweating or in contact with water, resulting in a mottled makeup. In addition, existing oil-control powders often appear thick and fake visually, lacking a natural skin texture, and cannot meet the needs of modern consumers for a light, natural makeup look. Therefore, it is necessary to develop a powder that can effectively control oil and has waterproof properties while also providing a high-end makeup feel. Summary of the invention
[0004] In order to develop a powder that can effectively control oil and has waterproof properties, and can also provide a high-end makeup feeling, the present application provides a waterproof oil-control powder with a soft focus effect, and a preparation method and application thereof. The soft focus effect waterproof oil-control powder of the present invention not only has good oil control performance, but also can form a waterproof film on the skin surface, effectively preventing sweat and moisture from damaging the makeup, while improving the skin texture through the soft focus effect, making the makeup more natural and lasting.
[0005] In the first aspect, the present application provides a waterproof and oil-control powder with a soft focus effect, which adopts the following technical scheme: a waterproof and oil-control powder with a soft focus effect, comprising the following raw materials in percentage by mass: 60% to 70% synthetic fluorphlogopite, 8% to 12% vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, 18% to 22% silica, 1% to 3% triethoxycaprylylsilane, 4% to 5% zinc oxide, 0.5% to 1% trimethylsiloxysilicate and 0.5% to 1% capryloyl glycine.
[0006] In the above technical scheme, this application not only solves the shortcomings of traditional makeup products in oil control and waterproofing through the specific selection of various raw materials, but also can effectively reduce light reflection, create a natural soft focus effect, make the skin look more delicate and smooth, enhance the naturalness and durability of makeup, and achieve the multi-functionality of powder in waterproofing, oil control and soft focus. By choosing synthetic fluorphlogopite as the main ingredient of the powder, synthetic fluorphlogopite has good covering power and soft focus effect, good ductility on the face, good skin adhesion, and can form a uniform film on the skin surface to enhance the natural feeling of the makeup effect; vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer makes the powder soft and elastic; the addition of silica enhances the adsorption capacity of the powder, effectively controls sebum secretion, and keeps the makeup fresh; triethoxycaprylylsilane, as a hydrophobic agent, further enhances the waterproof effect of the powder; zinc oxide, as a broad-spectrum physical sunscreen, can reflect and scatter UVA and UVB radiation, providing immediate and continuous UV protection, and the combination of trimethylsiloxysilicate and capryloyl glycine not only further ensures the proper moisture balance of the skin and prevents the makeup from drying out, but also further enhances the adhesion and waterproofness of the powder, ensuring that the zinc oxide particles form a stable and non-detachable protective layer on the skin surface, assisting in combating free radicals generated by UV irradiation, further enhancing the UV protection effect of the powder, and protecting the skin barrier function.
[0007] Preferably, the mass ratio of zinc oxide, trimethylsiloxysilicate and capryloyl glycine is 4.8:0.72:0.9.
[0008] In the above technical scheme, the present application achieves the optimal synergistic effect between the ingredients by further limiting the mass ratio of zinc oxide, trimethylsiloxysilicate and capryloyl glycine to 4.8:0.72:0.9. Under this ratio, zinc oxide can fully exert its sunscreen and oil-control effects, while trimethylsiloxysilicate and capryloyl glycine effectively enhance the adhesion and moisturizing properties of the powder, making the makeup both long-lasting and natural.
[0009] Preferably, the particle size of the synthetic fluorphlogopite is between 9 and 11 μm.
[0010] Preferably, the particle size of the silicon powder is between 6 and 8 μm.
[0011] In the above technical solution, by controlling the particle size of synthetic fluorphlogopite between 9 and 11 μm, it can provide good covering power without giving a heavy feeling to the skin; the particle size of silica is controlled between 6 and 8 μm, which can effectively absorb oil without clogging pores, keeping the skin breathing smoothly.
[0012] In the second aspect, the present application provides a method for preparing a waterproof and oil-controlling powder with a soft focus effect, which adopts the following technical solution: A method for preparing a waterproof and oil-controlling powder with a soft-focus effect, comprising the following steps: Step 1: Mix synthetic fluorphlogopite, silica and vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, add hydrogen peroxide as a medium, and stir evenly; Step 2: Add triethoxyoctylsilane to the material obtained in step 1, use a kneading device to mix for 10 minutes, and then stir for 50 minutes to mix the material into a dough state; Step 3: Add zinc oxide and capryloyl glycine to the material obtained in step 2, continue to use the kneading equipment to mix for 10 minutes, and then stir for 20 minutes to keep the material in a dough state; Step 4: Add trimethylsiloxysilicate to the material obtained in step 3, continue to use the kneading equipment to mix for 10 minutes, and then stir for 20 minutes to keep the material in a dough state; Step 5: Put the material obtained in step 4 into an oven, adjust the temperature to 98°C, bake until the medium is completely volatilized, crush and sieve to obtain a waterproof and oil-control powder with a soft focus effect.
[0013] In the above technical scheme, the present application modifies the surface of the powder by using triethoxycaprylylsilane, and through the combination of hydrogen peroxide, kneading and stirring processes, ensures that under the mechanical and chemical combination treatment, triethoxycaprylylsilane can fully adhere to the surface of synthetic fluorphlogopite and silica, forming a stable material basis, and further adds zinc oxide, caprylyl glycine and trimethylsiloxysilicate to ensure the comprehensive performance of the powder, and further refines the powder particles through crushing and sieving treatment, improves its uniformity and fineness, and ensures that the final product can present the best makeup effect and touch when used.
[0014] Preferably, the beating speed of step 2 is 100 r / min, and the stirring speed is 5000 r / min; the beating speed of step 3 is 100 r / min, and the stirring speed is 5000 r / min; the beating speed of step 4 is 100 r / min, and the stirring speed is 5000 r / min.
[0015] In the above technical solution, the present application ensures that the raw materials are evenly distributed during the mixing process to form a stable composite structure by precisely controlling the beating and stirring speed in each step, thereby improving the overall performance and use effect of the powder.
[0016] In a third aspect, the present application provides a waterproof oil-control powder with a soft-focus effect, which is applied in cosmetics using the following technical solution: The invention discloses an application of a waterproof oil-control powder with a soft focus effect in cosmetics, and the waterproof oil-control powder with a soft focus effect is used in setting cosmetics.
[0017] In the above technical scheme, the waterproof oil-control powder with soft focus effect of the present application not only has good oil control and waterproof properties, but also can form a delicate soft focus effect on the skin surface, making the makeup more natural and lasting, and meeting the needs of modern consumers for high-quality cosmetics.
[0018] Preferably, the setting makeup cosmetics include but are not limited to pressed powder, loose powder, honey powder, setting spray and the like.
[0019] In the above technical scheme, the waterproof and oil-control powder with soft focus effect of the present application can be widely used in a variety of makeup products, whether it is pressed powder, loose powder, honey powder or setting spray, which can significantly improve the makeup setting effect of the product.
[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application provides a powder that combines waterproof, oil-control and soft-focus effects, which can be used in setting cosmetics to significantly improve the setting performance of setting products.
[0021] 2. This application adds zinc oxide, capryloyl glycine and trimethylsiloxysilicate to the powder, which can effectively protect the skin while maintaining long-lasting makeup and enhance the powder's ability to protect the skin barrier. DETAILED DESCRIPTION
[0022] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0023] Example 1 A waterproof oil-control powder with a soft-focus effect comprises 615.8 g of synthetic fluorphlogopite, 100 g of vinyl dimethicone / methicone silsesquioxane cross-linked polymer, 200 g of silica, 20 g of triethoxycaprylylsilane, 48 g of zinc oxide, 7.2 g of trimethylsiloxysilicate and 9 g of capryloyl glycine.
[0024] Among them, the synthetic fluorphlogopite is homemade and has a particle size of 10 μm.
[0025] Among them, the silicon powder is homemade and has a particle size of 7μm.
[0026] Vinyl dimethicone / polymethylsiloxane silsesquioxane cross-linked polymer was purchased from Hunan Siluoke Organic Silicone Co., Ltd., item number: Sicare 2187P8.
[0027] Among them, triethoxyoctylsilane was purchased from Nanjing Nengde New Material Technology Co., Ltd., item number: SCA-K08E.
[0028] Among them, zinc oxide was purchased from Shandong Leander Biotechnology Co., Ltd., density: 5.606g / cm 3 .
[0029] Among them, trimethylsiloxysilicate was purchased from Jining Fangyu Chemical Co., Ltd., product number: German BELSILTMS 803.
[0030] Among them, capryloyl glycine was purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd., product number: XK0127.
[0031] The method for preparing the waterproof and oil-control powder with a soft-focus effect comprises the following steps: Step 1: Mix synthetic fluorphlogopite, silica and vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, add hydrogen peroxide as a medium, and stir evenly; Step 2: Add triethoxyoctylsilane to the material obtained in step 1, and use a kneading device to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 50 minutes to mix the material into a dough state; Step 3: Add zinc oxide and capryloyl glycine to the material obtained in step 2, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 4: Add trimethylsiloxysilicate to the material obtained in step 3, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 5: Put the material obtained in step 4 into an oven, adjust the temperature to 98°C, bake until the medium is completely volatilized, crush and sieve to obtain a waterproof and oil-control powder with a soft focus effect.
[0032] Example 2 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that it includes 635g of synthetic fluorphlogopite, 80g of vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane crosspolymer, 220g of silica, 10g of triethoxycaprylylsilane, 40g of zinc oxide, 10g of trimethylsiloxysilicate and 5g of capryloyl glycine.
[0033] The method for preparing the waterproof and oil-control powder with a soft-focus effect comprises the following steps: Step 1: Mix synthetic fluorphlogopite, silica and vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, add hydrogen peroxide as a medium, and stir evenly; Step 2: Add triethoxyoctylsilane to the material obtained in step 1, and use a kneading device to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 50 minutes to mix the material into a dough state; Step 3: Add zinc oxide and capryloyl glycine to the material obtained in step 2, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 4: Add trimethylsiloxysilicate to the material obtained in step 3, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 5: Put the material obtained in step 4 into an oven, adjust the temperature to 98°C, bake until the medium is completely volatilized, crush and sieve to obtain a waterproof and oil-control powder with a soft focus effect.
[0034] Example 3 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that it includes 605g of synthetic fluorphlogopite, 120g of vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane crosspolymer, 180g of silica, 30g of triethoxycaprylylsilane, 50g of zinc oxide, 5g of trimethylsiloxysilicate and 10g of capryloyl glycine.
[0035] The method for preparing the waterproof and oil-control powder with a soft-focus effect comprises the following steps: Step 1: Mix synthetic fluorphlogopite, silica and vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, add hydrogen peroxide as a medium, and stir evenly; Step 2: Add triethoxyoctylsilane to the material obtained in step 1, and use a kneading device to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 50 minutes to mix the material into a dough state; Step 3: Add zinc oxide and capryloyl glycine to the material obtained in step 2, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 4: Add trimethylsiloxysilicate to the material obtained in step 3, continue to use the kneading equipment to mix at a speed of 100 r / min for 10 minutes, and then mix at a stirring speed of 5000 r / min for 20 minutes to mix the material into a dough state; Step 5: Put the material obtained in step 4 into an oven, adjust the temperature to 98°C, bake until the medium is completely volatilized, crush and sieve to obtain a waterproof and oil-control powder with a soft focus effect.
[0036] Comparative Example 1 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that zinc oxide, trimethylsiloxysilicate and capryloyl glycine are replaced by synthetic fluorphlogopite in equal amounts.
[0037] Comparative Example 2 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that trimethylsiloxysilicate and capryloyl glycine are replaced with synthetic fluorphlogopite in equal amounts.
[0038] Comparative Example 3 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that an equal amount of zinc oxide is replaced by synthetic fluorphlogopite.
[0039] Comparative Example 4 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that trimethylsiloxysilicate is replaced with polyvinyl pyrrolidone in an equal amount, and is purchased from Hangzhou Hengquan Technology Development Co., Ltd., item number: 9003-39-8.
[0040] Comparative Example 5 A waterproof and oil-control powder with a soft-focus effect, which is different from Example 1 in that an equal amount of capryloyl glycine is replaced with zinc pyroglutamate and is purchased from Wuhan Xingzhongcheng Technology Co., Ltd.
[0041] Performance Testing 1. Soft focus test Test samples: silica, synthetic fluorphlogopite, and the oil-control powder of Example 1 of the present application.
[0042] Test method: On the back skin of the same person, divide three areas of equal size and use oil at (0.1±0.02)g / cm 2 Apply a single application of the amount of the powder, then take the same amount of the test sample, use a powder puff to gently and evenly press the test sample into the specified area, and compare the soft focus effect of the area after the powder is pressed. The observation results are shown in Table 1.
[0043] Table 1: Combining Table 1 and the analysis of the three test samples of silica, synthetic fluorphlogopite, and the oil-control powder of Example 1 of the present application, it can be seen that the oil-control powder of the present application has a good soft-focus effect, can well hide pores, and smooth the skin surface.
[0044] 2. Oil control test Test samples: the oil-control powders, silica and synthetic fluorphlogopite of the above-mentioned embodiments and comparative examples.
[0045] Test method: 100 subjects were selected and randomly divided into 10 groups, with 10 subjects in each group. Under the supervision of the test personnel, the subjects cleaned the test area with an alkaline soap-based cleaning product, rinsed it with clean water, and then dried it with a non-chip absorbent dry paper towel. Within 3 minutes, the amount of sebum on the skin surface of the sample application area and the control area was measured and recorded using a skin sebum tester. Each sample was measured at (2.0±0.1) mg / cm 2 Apply the sample once with the dosage of 100 mg / ml and evenly apply the sample to the specified area using a latex fingertip. Measure the sample application area every 1 hour to obtain and record the amount of sebum on the skin surface. When measuring at different measurement time points, avoid the positions that have been measured. The entire test cycle usually does not exceed 12 hours. During the test, when the amount of sebum on the skin surface obtained by the test increases significantly, the last measurement time point is used as the final makeup holding time and recorded. The makeup holding time of each group is expressed as an average value, see Table 2.
[0046] Table 2: Test samples Makeup lasting time (h) Example 1 10.9 Example 2 10.6 Example 3 10.7 Comparative Example 1 9.2 Comparative Example 2 9.5 Comparative Example 3 9.8 Comparative Example 4 10.1 Comparative Example 5 10.3 Silica 6.3 Synthetic Fluorphlogopite 5.7 Specifically combined with Examples 1 to 3, Comparative Examples 1 to 5, silica, synthetic fluorphlogopite and Table 2 analysis, it can be seen that the oil control powder of the present application shows a long makeup holding time in each embodiment. Specifically, the average makeup holding time of Examples 1 to 3 is between 10.6 and 10.9 hours, while the makeup holding time of Comparative Examples 1 to 5 is between 9.2 and 10.3 hours, and the makeup holding time of silica and synthetic fluorphlogopite is 6.3 hours and 5.7 hours, respectively. This shows that the oil control powder of the present application not only has a good soft focus effect, but also can effectively control oil, prolong the makeup holding time of makeup, and improve the stability and durability of the overall makeup effect. More specifically, the three ingredients of zinc oxide, capryloyl glycine and trimethylsiloxysilicate added in the present application also play an important role in improving the oil control of the oil control powder.
[0047] 3. Waterproof test Test samples: the oil-control powders, silica and synthetic fluorphlogopite of the above-mentioned embodiments and comparative examples.
[0048] Detection method: Contact angle test: The contact angle between the sample and water is tested. The test results are shown in Table 3.
[0049] Table 3: Specifically combining Examples 1 to 3, Comparative Examples 1 to 5, silica, synthetic fluorphlogopite and Table 2, it can be seen that the oil-control powder of the present application performs well in terms of waterproof performance. The contact angle test results show that the contact angles of Examples 1 to 3 are all above 138°, which indicates that the present application effectively improves the waterproof effect of the oil-control powder by adding zinc oxide, capryloyl glycine and trimethylsiloxysilicate.
[0050] 4. User experience evaluation Test sample: the oil-control powder of the above-mentioned embodiments and comparative examples.
[0051] Testing method: 80 volunteers aged 18 to 40 who met the test requirements were selected as test subjects. All of them had oily skin according to the Bergman Questionnaire. They were randomly divided into 8 groups, with 10 people in each group. The subjects cleaned their faces every day and dried their skin with dry facial tissues. After using the same products for skin care, they used the same products for makeup. The subjects evenly applied foundation on their faces, then gently dipped an appropriate amount of the test sample with a puff and patted their faces. After using it for one month, the subjects evaluated the skin feel, makeup lasting effect, and skin barrier protection ability of the test samples. The evaluation criteria are as follows: Skin Feel: 5 points: Very comfortable, no discomfort; 4 points: relatively comfortable, with slight discomfort; 3 points: general, no obvious discomfort; 2 points: Slight discomfort, but does not affect use; 1 point: Very uncomfortable, unbearable.
[0052] Long-lasting makeup effect: 5 points: The makeup lasts for more than 10 hours and the makeup is intact; 4 points: makeup lasts 8 to 10 hours, with slight makeup removal; 3 points: makeup lasts for 6 to 8 hours, and makeup comes off obviously; 2 points: makeup lasts 4 to 6 hours, and is seriously removed; 1 point: Makeup lasts less than 4 hours and comes off completely.
[0053] Skin barrier protection ability: 5 points: Skin condition is significantly improved and the skin becomes healthier; 4 points: some improvement, and the skin condition is relatively stable; 3 points: no obvious change, skin condition remains the same; 2 points: Slightly deteriorated, but does not affect daily use; 1 point: Significant deterioration, with skin discomfort.
[0054] According to the evaluation results of the subjects, the average score of each test sample was calculated, and the results are shown in Table 4.
[0055] Table 4: Specifically, it can be seen from the data analysis of Examples 1 to 3, Comparative Examples 1 to 5, and Table 4 that Examples 1 to 3 scored well in terms of skin feel, makeup lasting effect, and skin barrier protection ability. The subjects generally reported that the skin feel was good, the makeup lasted for a long time, and the skin barrier was well protected. This shows that after adding zinc oxide, capryloyl glycine, and trimethylsiloxysilicate, the protective ability of the oil-control powder on the skin barrier is further improved.
[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A waterproof and oil-control powder with a soft-focus effect, characterized in that: The invention comprises the following raw materials in percentage by mass: 60% to 70% of synthetic fluorphlogopite, 8% to 12% of vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, 18% to 22% of silica, 1% to 3% of triethoxycaprylylsilane, 4% to 5% of zinc oxide, 0.5% to 1% of trimethylsiloxysilicate and 0.5% to 1% of capryloyl glycine.
2. The waterproof and oil-controlling powder with soft-focus effect according to claim 1, characterized in that: The mass ratio of the zinc oxide, trimethylsiloxysilicate and capryloyl glycine is 4.8:0.72:0.
9.
3. The waterproof and oil-controlling powder with soft focus effect according to claim 1, characterized in that: The particle size of the synthetic fluorphlogopite is between 9 and 11 μm.
4. The waterproof and oil-controlling powder with soft focus effect according to claim 1, characterized in that: The particle size of the silicon powder is between 6 and 8 μm.
5. A method for preparing the waterproof and oil-controlling powder with soft focus effect according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Mix synthetic fluorphlogopite, silica and vinyl polydimethylsiloxane / polymethylsiloxane silsesquioxane cross-linked polymer, add hydrogen peroxide as a medium, and stir evenly; Step 2: Add triethoxyoctylsilane to the material obtained in step 1, use a kneading device to mix for 10 minutes, and then stir for 50 minutes to mix the material into a dough state; Step 3: Add zinc oxide and capryloyl glycine to the material obtained in step 2, continue to use the kneading equipment to mix for 10 minutes, and then stir for 20 minutes to keep the material in a dough state; Step 4: Add trimethylsiloxysilicate to the material obtained in step 3, continue to use the kneading equipment to mix for 10 minutes, and then stir for 20 minutes to keep the material in a dough state; Step 5: Put the material obtained in step 4 into an oven, adjust the temperature to 98°C, bake until the medium is completely volatilized, crush and sieve to obtain a waterproof and oil-control powder with a soft focus effect.
6. The method for preparing a waterproof and oil-controlling powder with a soft focus effect according to claim 5, characterized in that: The beating speed of step 2 is 100 r / min, and the stirring speed is 5000 r / min; the beating speed of step 3 is 100 r / min, and the stirring speed is 5000 r / min; the beating speed of step 4 is 100 r / min, and the stirring speed is 5000 r / min.
7. Use of the waterproof and oil-controlling powder with soft focus effect as claimed in any one of claims 1 to 4 in cosmetics, characterized in that: Use waterproof, oil-control powder with a soft-focus effect for setting makeup.
8. The use of the waterproof oil-controlling powder with soft focus effect in cosmetics according to claim 7, characterized in that: The makeup-setting cosmetics include but are not limited to pressed powder, loose powder, honey powder, makeup-setting spray, etc.
Citation Information
Cited By
Preparation method and application of oil-control anti-darkness cosmetic composition
CN121533924A